KLITIK PRONOMINA CERPEN DALAM MAJALAH BOBO: PENUNJANG LITERASI, STRUKTUR KALIMAT, DAN KESANTUNAN BERBAHASA INDONESIA PADA FASE B TINGKAT SEKOLAH DASAR - Ramadhani, Azila Fitria; Putri, Dea Maulidya; Mahmudah, Ripaatil; Kusumah, Encep (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2025)
This study aims to describe the use of pronominal clitics in Bobo Magazine's short story collection and see its potential in supporting the Indonesian language learning process in phase B of the elementary school level. The method used in this research is descriptive qualitative with data collection techniques in the form of literature study. The data analysis technique uses literature study with listening and recording techniques. The data of this research are pronominal clitics found in short stories published in Bobo Magazine from February to April 2025, namely: 1) Idol Hero, 2) Grandfather's Barong Mask, and 3) Half Day Fasting. The results show that there are two types of pronominal clitics, namely proclitics {ku-}, {kau-} and enclitics {-ku}, {-mu}, {-nya}, with uneven distribution. Enclitics, especially {-nya}, are most dominantly used, reflecting the use of third-person point of view in children's short story narratives. In contrast, the form {kau-} was absent and {-mu} appeared in limited numbers, indicating a subtle and indirect narrative tendency in children's communication. The conclusion of this study is that pronominal clitics, with their rich variety of forms and functions, have great potential to be utilized as teaching materials that are contextual, functional, and in accordance with students' cognitive development level.